Le Livre des Haltes (Kitâb al-Mawâqif), Tome II - Lagarde, Michel (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This second volume, out of three, contains the chapters 216 up to 320 of the alltogether 372 chapters. Based on the Dār al-yaqaza al-'arabiyya (1966-1967) and on the manuscript of the Library of Alger, this translation has taken into account the work accomplished by Michel Chodkiewicz (Éditions du Seuil, 1982) and by A. Khurshīd (Alif Ëditions, 1996). It deals with mystic comments on Qur'anic verses and prophetic translations inspired by Ibn 'Arabi's work. This volume also contains long comments on the Futuḥāt . Chapter 248 deals with the synthesis of Shaykh al-Akbar's view on the world, which helps to get an idea of this rather well organised vision, which is however often hard to understand.